Uterine cytokine profiles after low-molecular-weight heparin administration are associated with pregnancy outcomes of patients with repeated implantation failure - Niu, Zhihong; Zhou, Mingjuan; Xia, Lan; Zhao, Shen; Zhang, Aijun (Frontiers in Endocrinology, 2022)
Low molecular-weight heparin (LMWH) plays a role in repeated implantation failure (RIF), but outcomes are controversial. LMWH can potentially modulate local immune responses associated with the establishment and maintenance of pregnancy. The study aimed to explore the effects of LWMH in uterine inflammatory cytokine profiles and pregnancy outcomes of patients with repeated implantation failure (RIF) but without thrombophilia. we compared clinical characteristics and reproductive outcomes among 326 patients with RIF, but not thrombophilia, undergoing frozen embryo transfer (FET) cycle with or without LMWH treatment. Endometrium secretions were aspirated from both groups after 3 days of progesterone administration before and after LMWH treatment. Cytokine mRNA expression was analyzed in primary endometrial cells in vitro. The clinical and ongoing pregnancy rates did not significantly differ between the groups (31.5% vs. 24.4%, p = 0.15; 29.6% vs. 20.7%, p = 0.06). Concentrations of IL-6 and granulocyte-colony stimulating factor (G-CSF) in uterine secretions were significantly increased in the LWMH group, regardless of pregnancy outcomes (P < 0.05). And, in all patients treated with LWMH, those of secreted IL-6, IL-15 and G-CSF were significantly increased in pregnant group (P < 0.05). The expression of mRNA for G-CSF and IL-6 was significantly increased in human endometrial stromal cells in vitro (P < 0.05) after stimulation with LWMH (10 IU/mL).